Feasibility and resource utilization of nurse-administered subcutaneous immunoglobulin therapy in antibody deficiency: A cross-sectional study - Darshee Ghia; Pranavi Thota; Taylor Ritchie; Heli Rana; Ranvir Minhas; Jalal Moolji; Bruce Ritchie; Adil Adatia (PLoS ONE, 2025)
Primary and secondary antibody deficiencies (PAD and SAD) are amongst the most prevalent immunodeficiency syndromes, often necessitating long-term immune globulin replacement therapy (IRT). Both intravenous immunoglobulin (IVIG) and subcutaneous immunoglobulin (SCIG) have demonstrated efficacy in antibody deficiency. Comparative analyses of these two routes of administration are limited to nurse-administered IVIG and home therapy with self-administered SCIG. A third programmatic approach, SCIG administered by nurses in hospital-based outpatient infusion clinics, combines certain advantages of IVIG and home SCIG such as the provision of nursing support and the reduced risk of systemic reactions associated with the subcutaneous route. This cross-sectional study aimed to compare the viability and resource utilization of nurse-administered SCIG with IVIG in patients with antibody deficiency. We hypothesized that nurse-administered SCIG would require a similar amount of infusion clinic time per month as IVIG, despite more frequent dosing, due to shorter individual appointments, while maintaining high patient satisfaction. Information on infusion duration, time in the infusion chair, direct nursing time, and treatment satisfaction using the Life Quality Index was collected. Time measures for each patient were expressed as minutes/4 weeks to account for the more frequent dosing of nurse-administered SCIG compared to IVIG. We determined that the total time, infusion time, and nursing time needed to provide nurse-administered SCIG was comparable to IVIG. The more frequent dosing of SCIG was offset by the shorter times required per infusion. Patients reported favorable treatment satisfaction with both nurse-administered SCIG and IVIG. We conclude that nurse-administered SCIG may be a useful treatment modality for well-selected individuals.